The effect of intercropping with Pandanus amaryllifolius Roxb. on rhizospheric microorganism of Areca catechu L. - Ang Zhang; Fan Su; Xiaowei Qin; Huan Yu; Yiming Zhong; Xunzhi Ji; Shuzhen He; Ying Zong; Na An; Lihua Li; Susen Chen (iScience)
Summary: The intercropping pattern promotes the sustainable development of efficient agriculture, especially cash crops, such as Areca catechu L. and Pandanus amaryllifolius Roxb. intercropping plantation in China. However, the mechanisms underlying intercropping pattern effects on soil microbial community diversity and composition are poorly understood. A monoculture and intercropping field experiment of the two crops was established to monitor the changes of soil physicochemical properties, enzyme activities, microbial (bacterial and fungal) diversity, and composition. Soil bacterial rather than fungal communities’ diversity is more sensitive to intercropping pattern. The intercropping significantly decreased rhizospheric bacterial diversity of Areca catechu L. by 4.21%, and the decrease of soil nutrient content may be the main reason for the change of soil enzyme activity, bacterial community diversity, and composition structure under intercropping pattern. Supplementing nutrients to the soil of intercropping systems is conducive to maintain soil health and ecosystem functional stability in the tropical compound cultivation plantation.